ANALISIS KESULITAN SISWA DALAM PROSES PEMBELAJARAN ONLINE MATA PELAJARAN GEOGRAFI DI SMA NEGERI 1 X KOTO KABUPATEN TANAH DATAR - Cintia Chairani; Surtani Surtani (JURNAL BUANA, 2022)
This study aims to identify the student’s difficulties experience in online Geography learning process and the underlying factors also the strategy to slove them at the SMA Negeri 1 X Koto, Tanah Datar district. The type of this research is descriptive quantitative. This research was conducted in SMAN 1 X Koto. The sample in this study was determined by an involuntary sampling technique, which is a deliberate analysis of the data-sources samples by propagating the research apparatus through Google Form. This study found : 1) students are less interested, unmotivated and hard to concentrate with online learning systems. The underlying factors include, first is internal factors such as health disorder. Whereas the external causes are, lack of online learning tools like laptops, computers and smartphones, not exactly adequate in the internet package and teh living conditions are not conducive to learning. 2) The strategy to solve the learning difficulties are come from teacher, parents and the student.